a)
Metoda podstawiania
x - 3y = 13 ⇒ x = 3y + 13
-2x + y = -6
-2(3y+13) + y = -6
-6y - 26 + y = -6
-5y = -6 + 26
-5y = 20 /:(05)
y = -4
x = 3y + 13 = 3 · (-4) + 13 = -12 + 13
x = 1
{x = 1
{y = -4
b)
2x + 6y = -2 /:2
5x + 15 y = 0 /:5
x + 3y = -1
x + 3y = 0
---------------- - (odejmujemy stronami)
0 = -1, sprzeczność, brak rozwiązań
0 ≠ -1
c)
x - 3y = 1 /·3
-3x + 9y = -3
3x - 9y = 3
-3x + 9y = -3
--------------------- + (dodajemy stronami)
0 = 0, równanie tożsamościowe, nieskończenie wiele rozwiązań